Memory programmes: the industrial retention of collective life. - Kinsley, Samuel (Cultural Geographies, 2015)
This article argues that in software, we have created quasi-autonomous systems of memory that influence how we think about and experience life as such. The role of mediated memory in collective life is addressed as a geographical concern through the lens of ‘programmes’. Programming can mean ordering, and thus making discrete, and scheduling, making actions routine. This article addresses how programming mediates the experience of memory via networked technologies. Materially recording knowledge, even as electronic data, renders thought mentally and spatially discrete and demands systems to order it. Recorded knowledge also enables the ordering of spatiotemporal experience both as forms of history, thus the sharing of culture, and as the means of imagining futures. We increasingly retain information about ourselves and others using digital media. We volunteer further information recorded by electronic service providers, search engines and social media. Many aspects of our collective lives are now gathered in cities (via closed-circuit television, cellphone networks and so on) and retained in databases, constituting a growing system of memory of parts of life otherwise forgotten or unthought. Using examples, this article argues that in software, we have created industrialised systems of memory that influence how we think about living together.